Does microcredit reach the poor and most vulnerable in era of pandemic? – evidence from Nigeria (2021)
The study examined the impact of Covid-19 pandemic on households’ income and consumption – two economic measures used in measuring poverty. The study also assessed whether households especially those in rural areas are able to access microcredit because microcredit is a global recognised poverty alleviation strategy. It is widely recognized that access to micro-credit in developing countries empowers the poor (especially women) while supporting income-generating activities, encouraging the entrepreneurial spirit, and reducing vulnerability to shocks. The mixed method approach was adopted by the study. First, the study reviews the state of microcredit delivery in rural communities in Nigeria, identifies policy gaps in microcredit delivery and highlights the linkages between microcredit and poverty alleviation. Secondly, the study using a survey of selected rural communities, assessed whether households are able to access microcredit and other government palliatives put in place to mitigate the impact of the pandemic. The study found that majority of households could not access microcredit from formal microfinance institutions instead majority of the households’ resorted to informal institutions with attendant high cost of interest while government palliatives were non-existent in the communities surveyed. The study recommended that acknowledging the role of the informal actors in microcredit delivery is the critical first step towards framing a sustainable microcredit delivery policy in which both the formal and informal institutions are involved in microcredit delivery and governance.